A questão do gabarito na orla marítima de João Pessoa (bairros de Manaíra, Tambaú e do Cabo Branco) - Moreira, Raphaela Cristhina Claudino (2006)
This work discusses the stepped control of building heights in three seashore districts of João Pessoa-PB, Brazil Cabo Branco, Tambaú e Manaíra , with a view to grasp the principles and concepts underlying the adoption of that instrument. The discussion of the issue required an analysis of the relations between density and the performance of the urban organism. A simulation was made to foresee the densification of a sample of Tambaú district following the present legislation and the tendencies of the property market and the impact of this densification on the local traffic was pointed out. The research has shown that the instrument in question and the other relevant legislation are not able to control effectively the local density